2019
DOI: 10.1186/s12967-019-2060-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentration and expression of adipokines in epicardial and subcutaneous adipose tissue are associated with impaired left ventricular filling pattern

Abstract: Background Adipokines in serum derive mainly from subcutaneous and visceral adipose tissues. Epicardial adipose tissue (EAT), being a relatively small but unique fat depot, probably does not make an important contribution to systemic concentrations of adipokines. However, proximity of EAT to cardiac muscle and coronary arteries allows cells and proteins to penetrate between tissues. It is hypothesized that overexpression of proinflammatory cytokines in EAT plays an important role in pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 38 publications
2
31
1
3
Order By: Relevance
“…The high level of resistin and IL-6 was correlated with LVH and systolic dysfunction in Toczylowski et al 37 On ROC analysis of NT-proBNP, its cut-off level was 444.13 pg/ml, with an AUC of 0.987 (p<0.001), sensitivity of 100% and specificity of 92.6%, which mean that NT-proBNP is a novel, sensitive, specific predictor biomarker for T2DM.…”
Section: Discussionmentioning
confidence: 93%
“…The high level of resistin and IL-6 was correlated with LVH and systolic dysfunction in Toczylowski et al 37 On ROC analysis of NT-proBNP, its cut-off level was 444.13 pg/ml, with an AUC of 0.987 (p<0.001), sensitivity of 100% and specificity of 92.6%, which mean that NT-proBNP is a novel, sensitive, specific predictor biomarker for T2DM.…”
Section: Discussionmentioning
confidence: 93%
“…According to a systematic review and metaanalysis by Polyzos et al [199], higher circulating leptin levels were seen in NAFL and NASH when compared to healthy controls, and in NASH when compared to NAFL. Increased serum J o u r n a l P r e -p r o o f leptin levels also correlated with increased NAFLD severity [199], and a recent study further showed that obesity and T2DM were associated with increased leptin and decreased adiponectin serum levels in patients with coronary artery disease [200]. In addition, higher protein expressions of leptin and IL-6 in subcutaneous adipose tissue (SAT) were observed in male patients with coronary artery disease [200].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 93%
“…Leptin has an oncogenic potential and stimulates the proliferation, tumor invasiveness and migration of HCC cell lines [201,207] and cholangiocarcinoma cells in vitro [208], while adiponectin antagonizes the oncogenic activity of leptin in HCC [201]. In addition, normal and malignant cholangiocytes express leptin and both long and short isoform of leptin receptors [200,208]. Overall increased leptin serum levels seem to be associated with carcinogenesis in obesity [209].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators believe that a high level of leptin is related to low arterial extensibility and participates in the pathogenesis of atherosclerosis via mechanisms different from vascular relaxation. Some authors have noted a connection between serum concentrations of leptin and various cardiovascular risks, including stroke, chronic heart failure, acute myocardial infarction, coronary artery disease, and left ventricle hypertrophy [30][31][32][33][34]. It seems worthwhile to study leptin/adiponectin ratios.…”
Section: Leptinmentioning
confidence: 99%